The Effects of Different Types of Strength Training for Recreational Purposes on the Body Composition and Strength Development of University Students - Özbay, Serhat (Asian Journal of Education and Training, 2019)
The aim of this study was to investigate the effect of CrossFit and resistance training on maximal strength, isometric strength and strength continuity in recreational student athletes. 28 healthy male volunteer students who were doing sport for recreational purposes participated in the study. After the participants were randomly divided into two groups, strength tests were performed and body composition measurements were taken before and after the 16-week training period. Bench press and squat were applied to determine maximal force; leg and handgrip strength were applied to determine isometric force; pull-up and push-up tests were applied to determine the continuity of strength. Body composition measurements were performed with electronic scales. Statistical analyses were performed with SPSS 21.0 program. Significance level was accepted as p <0.05. The CrossFit training program included consecutive 5 pull-ups, 10 push-ups and 15 squat exercises for 20 minutes (CrossFit-Cindy). Resistance training program consisted of 3 sets of bench press, lat pull down, leg press, biceps curl and triceps extension exercises with 3 minute intervals using 70% of the weights the participants could perform with pre-determined maximum 1 repetition. The results of the study showed that body fat percentages of both groups decreased significantly, performance variables increased significantly and body weight did not change significantly. In addition, the increase in push-up exercise was higher in the CrossFit group than in the resistance group. Thus, this study shows that although CrossFit training is short-termed, it can be used as an alternative to classical resistance training.